The question of the missing head : an Asperger's mystery - Copperman, E. J., 1957- (Copperman, E. J., 1957- Asperger's mystery, 2014)
Samuel Hoenig answers questions for a living. And as a man with Asperger's Syndrome, his unique personality helps him ferret out almost any answer there is. But his latest question is a rather odd one-- who stole a preserved head from the Garden State Cryonics Institute?